An optimal design tool for the design of continuous beam using Microsoft Excel - Lan, Jian (2015)
This project is a continuous project come from a last two-year final year program. The objectives of this project is to design an optimal design tool by using the Microsoft Excel 2013 to improve the code of steel beams to Eurocode 3 standard. By using this program, the structural engineers can design the continuous beam step by step, compute the design check and steel beam analysis. In this project, the objectives is to improve the efficiency when the engineers use this tool, to eliminate the need for manual design check and the design calculation and to reduce the possible human error. This report serves to show the development and improvement of the previous project, which are made by the Microsoft Excel spreadsheet program. The improvement of the design tool are according to the Eurocode 3 standard by using the Microsoft Excel 2013 and Visual Basic for Application (VBA) as the foundation to create the steel design program. The Microsoft Excel spreadsheet program include two main parts: The interface design will be introduced by the author’s partner, and the code behind will be covered by the author. In real construction industry, there are more buildings used more than two spans of beam and the live and dead load. Hence in this project, the improvement of the optimal design tool is to include more spans check in the steel design and add the live load and dead load factor to the load and moment. Some design details can be in accordance to the user mind to choose whether to see or not. The program also narrows the user screen, make sure they can follow the Eurocode 3 steel design check step by step to make the program more time efficient and reduce the mistake in the design check. Overall, this project has the step by step instructions to teach the user how to use. And it is useful for the structure engineers to do the design check in the real construction industry. The author and his partner are eager for see their spreadsheet program can be used in the real civil industry and serve as a reference for the civil engineering students to develop a further research to improve the similar spreadsheets design tool.